Clinical case of community-aquaired pneumonia on the background of previously undiagnosed occupational pulmonary fibrosis. Is occupational history important? - O. G. Cherkasova; I. O. Hutnik; G. D. Marynoha; O. A. Gusakova; G. V. Kondratieva; G. V. Danilova; O. V. Rozhko (Medičnì Perspektivi)
Interstitial lung disease is a systemic concept, which is understood as a group of progressive diseases, characterized by non-infectious inflammation in the wall of the alveoli and interstitial lung tissue and may result in pulmonary fibrosis. The publication deals with the clinical case of community-acquired pneumonia on the background of previously undiagnosed occupational pulmonary fibrosis. The complaints, anamnesis, clinical and instrumental data have been analyzed, special attention is paid to the professional history, which indicates long-term contact with toxic substances and negative factors of the industrial process. The data of pathomorphological research are given. Timely prevention and screening of workers involved in heavy work and work with harmful or hazardous working conditions, even after the cessation of work in a production environment, may contribute to early detection of interstitial lung disease and contribute to a positive prognosis for acute respiratory diseases occurring on its background.